The understanding of evidence-based medicine in undergraduate medical students: an integrative review (Research, Society and Development, 2022)
Evidence-based medicine (EBM) is defined as the conscious, explicit and judicious use of the best current evidence in making decisions about the care of individual patients. It has been associated with better clinical outcomes for patients, in addition to being an update tool for health professionals. Thus, evidence-based practice has been adopted in many schools around the world, despite this, it is practiced suboptimally, especially in developing countries. Thus, this work aims to answer the following question: "What knowledge do undergraduate medical students in the world have about EBM?", in addition to evaluating the different ways of teaching and behavioral changes after teaching EBM. Articles were collected in the MEDLINE and BSV databases, using the following descriptors: “Evidence-Based Medicine”, “Education, Medical, Undergraduate” during the month of October 2022. Subsequently, a careful analysis of the selected material was carried out in order to gather the most relevant information concerning the proposed theme. Eleven articles of the 111 found after using the exclusion criteria were included. It can be concluded, with this integrative review, that more studies are needed about the teaching of MBE in schools, in order to discover the best teaching method, when to start the EBM program at graduation, in addition to discovering which students' knowledge of EBM.